Tech-and entrepreneur-savvy add value to graduates - Mimi Rabita, Abdul Wahit (UMPSA, 2022)
KUANTAN, 6 August 2022 - Graduates of Universiti Malaysia Pahang (UMP) should be wise to take opportunities in line with current needs and involvement in entrepreneurship and technological intelligence that give added value to them.